Multinational financial management - Shapiro, Alan C.; Hanouna, Paul (Hoboken, NJ : Wiley, 2020)
'The basic thrust of this eleventh edition of Multinational Financial Management (MFM) is to provide a conceptual framework within which the key financial decisions of the multinational firm can be analyzed. The approach is to treat international financial management as a natural and logical extension of the principles learned in the foundations course in financial management. Thus, it builds on and extends the valuation framework provided by domestic corporate finance to account for dimensions unique to international finance. Multinational Financial Management presumes a knowledge of basic corporate finance, economics, and algebra. However, it does not assume prior knowledge of international economics or international finance and is therefore self-contained in that respect'--
Includes bibliographical references and index.
Buku bacaan asas prasiswazah Fakulti Ekonomi Pengurusan 2023/24.
Keywords: International business enterprises -- Finance